Pelatihan Pemanfaatan Sampah Anorganik Menjadi Meja Dan Kursi Dari Botol Plastik Bekas Di Dusun Nongkosongo Kabupaten Malang - Etik Puspitasari; Titis Agunging Tyas; Intan Fadhilah; Duratun Nasqiati Rosady; Ahsani Maulidina (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
The problem in Nongkosongo hamlet is residents' lack of awareness and knowledge about utilizing inorganic waste, as evidenced by the number of residents who register with the waste bank, only four from 3 RW. The methods used are coordinating with the village head, preparing tools and materials, providing training, holding competitions, and giving rewards. This activity aims to provide training in using inorganic waste to become added-value products in the form of tables and chairs from used plastic bottles. The second can make products with a teamwork system that is contested, and there is a reward system. The results obtained are training in making tables and chairs from used plastic bottles has been carried out. Second, making tables and chairs in teams with product results has been done, and rewards have been given. The products have been handed over and used in the waste bank as seats for guests.